A mutagenicity and cytotoxicity study on Limonium effusum aqueous extracts by Allıum, ames and MTT tests - Eren, Y.; Özata, A.; Konuk, M.; Akyil, D.; Liman, R. (Цитология и генетика, 2015)
Nowadays plants or plant extracts have become very important for alternative medicine. Plants and their extracts have many therapeutical advantages but some of them are potentially toxic, mutagenic, carcinogenic and teratogenic. Root, stem and leaf parts of Limonium effusum were used in this study and this species is an endemic species for Turkey. Mutagenic and cytotoxic effects of root, stem and leaf aqueous extracts were observed with Allium, Ames and MTT tests. Allium root growth inhibition test and mitotic index studies showed that aqueous extracts have dose-dependent toxic effects. Chromosome aberration studies indicated that especially sticky chromosome, anaphase-telophase disorder and laggard chromosome anomalies were highly observed. Ames test performed with Limonium effusum root aqueous extracts, showed weak mutagenic effects in Salmonella typhimurium TA98 strain with S9. MTT test based on mitochondrial activity indicated that most of the aqueous extracts have cytotoxic effects. This study aimed to determine the possible mutagenic and cytotoxic effects of L. effusum aqueous extracts by using bacterial, plant and mammalian cells. This research showed that some low concentrations of the L. effusum extracts have inhibited cytotoxic effects but high concentrations have induced cytotoxicity. On the other hand only a weak mutagenic activity was identified by Ames test with TA98 S9(+).